2019
DOI: 10.26822/iejee.2019248591
|View full text |Cite
|
Sign up to set email alerts
|

Philosophy for Children in Teacher Education: Effects, Difficulties, and Recommendations

Abstract: It is necessary to realize widespread and effective implementation of philosophy for children (P4C) in teacher education. Learning the views of teacher candidates and identifying implementation-related difficulties can help determine the content of such education. Thus, thirty teacher candidates who participated in an elective P4C course were studied. Data obtained through a qualitative study showed that the candidates struggled to ask questions, conduct debates, and associate philosophy with curricula. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
2
0
4
Order By: Relevance
“…In a study performed by Akkocaoğlu-Çayır (2018), teacher candidates were expected to develop PwC activities, implement these activities, and make self-evaluation. As a result, it was found that the teacher candidates have difficulties regarding asking questions and managing the discussion.…”
Section: Resultsmentioning
confidence: 99%
“…In a study performed by Akkocaoğlu-Çayır (2018), teacher candidates were expected to develop PwC activities, implement these activities, and make self-evaluation. As a result, it was found that the teacher candidates have difficulties regarding asking questions and managing the discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Öll hugsun felur að einhverju leyti þessa þaetti í sér og sérhver siðraen athöfn byggir á grunni þeirra. AEðri hugsun og heimspekilegar samraeður eiga erindi til flestra grundvallarþátta mannlegrar tilvistar (Çayır, 2018;Gaut og Gaut, 2011;Lipman, 1995;Matthews, 2000). Það sem greinir heimspekilegar samraeður í megindráttum frá öðrum samraeðum er einkum þrennt; að samraeðurnar hafi ákveðinn tilgang og þátttakendur laeri af þeim, að þátttakendur fari ekki á svig við sannleikann, að samraeðurnar varðveiti skilning og miðli honum frá einum til annars (Guðmundur Heiðar Frímannsson, 2018).…”
Section: Heimspeki Með Börnumunclassified
“…Hlutverk kennarans er mikilvaegt en hann á að gaeta þess að samraeður hafi heimspekilegt gildi og sjá til þess að þaer taki mið af markmiðum námskrár. Hlutverk kennarans er einnig að halda samraeðunum við málefnið án þess þó að taka stjórnina, spyrja spurninga, hlusta og virða skoðanir barnanna (Çayır, 2018;Gaut og Gaut, 2011).…”
Section: Heimspeki Með Börnumunclassified
See 2 more Smart Citations